(Unusual) weather and stock returns - I am not in the mood for mood: further evidence from international markets - Apergis, N.; Gabrielsen, A.; Smales, Lee (Springer, 2016)
This paper investigates the explanatory power of weather variables deviations in two leading international financial trading centres (New York and London) on 58 global stock indices over the period September 2000 to December 2013. The empirical results find that unusual deviations of weather variables from their monthly averages have a statistically significant effect on stock returns across global returns. The paper also attempts to explain these effects through the sales and energy prices mechanisms. The results provide strong support to both mechanisms.